2020
DOI: 10.18662/rrem/12.2/265
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Peculiarities of the First-Year Students to University Life: Study on Stress Resistance

Abstract: The paper is aimed at investigating adaptation peculiarities of the first-year students to university life. Among 105 first-year students selected for taking part in research 57 were internal migrants who had to change their place of residence and move to a student residential complex and 48 were original city residents who continued living at home. The research took place in 2018/2019 academic year at two Ukrainian universities. To promote research and collect data several diagnostic tools were used. To under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…The result of this study found that there was a significant correlation between psychological distress and academic adjustment. This data is congruent with Topuzov et al (2020); Hou et al (2020);Milic et al (2020), whereas there was an instance relationship between psychological distress and academic adjustment. In this data analysis, it was strongly suggested a statistically significant correlation between depression, general anxiety, social anxiety, and hostility toward academic adjustment, academic lifestyle, academic achievement, and academic motivation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The result of this study found that there was a significant correlation between psychological distress and academic adjustment. This data is congruent with Topuzov et al (2020); Hou et al (2020);Milic et al (2020), whereas there was an instance relationship between psychological distress and academic adjustment. In this data analysis, it was strongly suggested a statistically significant correlation between depression, general anxiety, social anxiety, and hostility toward academic adjustment, academic lifestyle, academic achievement, and academic motivation.…”
Section: Discussionsupporting
confidence: 90%
“…Hanawi et al (2020) stated that the life of a student might also be complicated due to learning activities and examinations, social life, hectic lifestyle and intolerance towards university life and climate. Topuzov, Shamne, Malykhin, Aristova, and Opaliuk (2020) disclosed the analysis by some scientists reveals that high academic and interpersonal tension among students during their first years corresponds with social exclusion and a high risk of suicide. As they further studied that this may cause by the lack of parents and friends' support and motivation, not having enough of the institute monitoring system, and personal matters.…”
Section: Introductionmentioning
confidence: 99%
“…The key requirement in the selection of psychodiagnostic tools is the relevant reflection of the subject of research. This methodology has been tested in the process of studying the parameters of emotional intelligence (Cheban et al, 2020;Halian, Halian, Burlakova et al, 2020), adaptation processes (Blynova, Chervinska et al, 2020;Blynova, Kisil et al, 2020;Kononenko et al, 2020;Shevchenko et al, 2020;Topuzov et al, 2020), innovation (Fizeshi, 2020;Tsiuniak et al, 2020), as well as in the study of educational processes and motivational states of young respondents (Blynova, Lappo et al, 2020;Halian, Machynska et al, 2020;Halian, Halian, Gusak et al, 2020). All these scientific researches are fully or partially connected with conformism and value orientations of young people.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…An absence or lack of emotional connections with significant Others and material insecurity, born by trauma, lead to hesitation in life goals. It is accompanied by usual challenges -stresses from examinations and adaptation to the HEI itself, that students overbear only by self-resistance (Topuzov et al, 2020). Sometimes the vulnerability forms paternalism and a dependent psyche, which significantly reduces the motivation to continue education, and can later lead to life failure (Bailey & Phillips, 2016;Bevz et al, 2020;Tate, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%